2013
DOI: 10.1111/pace.12240
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Implantable Electronic Device Infections in Left Ventricular Assist Device Recipients

Abstract: Background Most patients with left ventricular assist devices (LVAD) have concomitant cardiovascular implantable electronic devices (CIED). However, clinical presentation and outcome of CIED infection in the setting of LVAD has not been previously described. Methods We retrospectively reviewed 247 patients who underwent LVAD implantation at Mayo Clinic campuses in Minnesota, Arizona and Florida, from January 2005 to December 2011. Demographic and clinical data of patients that met criteria for CIED infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Based on our results, it appears reasonable to turn off the LV lead in CRT‐D patients following CF‐LVAD implant to save battery life and limit frequent pulse generator replacements. This is especially important given the higher risk of infection30 and periprocedural bleeding associated with procedures in the CF‐LVAD population.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, it appears reasonable to turn off the LV lead in CRT‐D patients following CF‐LVAD implant to save battery life and limit frequent pulse generator replacements. This is especially important given the higher risk of infection30 and periprocedural bleeding associated with procedures in the CF‐LVAD population.…”
Section: Discussionmentioning
confidence: 99%
“…The endovascular surface of LVAD must be presumed seeded in cases of implant device infection complicated by endocarditis. These cases should be managed with chronic suppressive antibiotic therapy until the infected LVAD is removed and replaced with a new device or until the patient undergoes cardiac transplantation (22). Conservative management of endocarditis without lead removal is reported as an ineffective treatment approach.…”
Section: Managementmentioning
confidence: 99%
“…Currently, there is no data regarding specific approaches in the management of LVAD endocarditis, device exchange or explantation is generally based on the patient's overall clinical status. In our review, out of the 8 patients reported with bacterial endocarditis among all the studies, all of them received a prolonged course of antibiotics, 2 patients had explantation of the device and one patient had an exchange of the inflow and outflow valves (2,(22)(23)(24)(25)(26). Aggressive management of infection, with prompt device removal and prolonged antibiotic therapy targeting the specific organism, is crucial to prevent catastrophic events (1).…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…One common theme among previously published studies is that the best predictor of appropriate ICD therapy after an LVAD is implanted is the presence of sustained VAs prior to implantation (ie, secondary prevention population). 24 Other questions that must be considered include the potential for and the management of infection in the setting of concomitant LVAD and cardiovascular implantable electronic device implantation, 25 and the safety and efficacy of LVAD implantation done in conjunction with that of newer technologies, such as subcutaneous ICDs. 26 The efficacy and benefits of cardiac resynchronization therapy device use in LVAD recipients also remains a topic of interest.…”
Section: Lvad Implantation In Icd Patientsmentioning
confidence: 99%